(untitled) (Bangladesh Journal of Medical Science, 2012)
Objective: To assess trends of smoking and the relation between smoking behavior of undergraduate medical students and their attitudes towards smoking and treatment of tobacco dependence. Methodology: Data was collected from the medical students of Rajshahi Islami Bank Medical College, Bangladesh. A total of 200 male students completed the anonymous questionnaire. Response rate was 80.0%. Results: Of the respondents 20% and 80% were regular smokers and non-smokers respectively. Only 32.50 % of the regular smokers smoke less than ten cigarettes, 30.0 % smoke ten to twenty cigarettes whereas, 37.50% smoke more than 20 cigarettes per day. 25% started smoking at nineteen years of age, 22.5% started before this age and 27.5% and 25.0 % started at twenty and twenty one years of ages respectively. 70% started smoking just for pleasure. Only 29.72% smoke light cigarettes whereas 33.78% and 36.48% smoke medium and heavy cigarettes respectively. Almost 75% smokers agreed with the fact that smoking is harmful to health and 45% realized that their cigarette smoke bother others and again 70% of smokers have attempted to quit smoking but failed and 42.5% still wanted to quit smoking. About 55% of smokers complained that they suffer from chronic cough, 60% were lacking concentration in their studies and 45% felt that they were short of memory. Conclusions: Attitudes of smokers were significantly different on most items of tobacco, but knowledge of tobacco problem in the undergraduate medical students was not sufficient. Teaching about tobacco and related issues remains essential in the undergraduate medical course. Key words: Smoking; hazardous; cigarette; students; medical rducation; vurriculum DOI: http://dx.doi.org/10.3329/bjms.v10i4.9501 BJMS 2011; 10 (4): 280-283